ANALISIS PENERAPAN PERLAKUAN AKUNTANSI PERSEDIAAN SESUAI DENGAN PERNYATAAN STANDAR AKUNTANSI KEUANGAN NOMOR 14 PADA PT MEGAH PRIMA SUPRA MAKMUR - Muhammad R B. Anwar; Jantje J. Tinangon; Robert Lambey (Universitas Sam Ratulangi, 2022)
Inventory is part of the assets held by the company with intention of business operations or using it for the production of goods to be sold. The problem that often occurs in companies is not reporting returns or damaged goods in the financial statements. At PT Megah Prima Supra Makmur, which has many types of products, its finansial statements do not include impairment of goods that have been damaged. The purpose of this study was to determine the application of the accounting treatment of inventories at PT Megah Prima Supra Makmur accordance with the Indonesia Accounting Standards Number 14 (PSAK No. 14).This type of research uses descriptive qualitative research in which researchers analyze inventory data and provide a detailed description of research results. In this study, the data source were obtained from interviews, observations, and documentation studies conducted at PT Megah Prima Supra Makmur.Based on the results of research that has been carried out, inventory measurement, cost recognition, and inventory disclosure are in accordance with PSAK No. 14, howeverthe company made mistake, namely not reporting damaged goods as a deduction from inventory on the income statement. The company also does not use inventory cards as part of inventory control. The results obtained after implementing the improvement are that the company’s financial statements are more reliable and also the control of inventory is getting better.